Analisis Dampak Dari Penggunaan Gawai Pada Anak Usia Dini Di Sekitar Rumah - Lase, Putri Nadila; Siregar, Mhd.Fuad Zaini (Pusdikra Publishing, 2024)
ICT (Information and Communication Technologies) refers to the broad category of technological tools used to process and communicate information. Gawais are one part of ICT that plays a crucial role in early childhood development. Advancements in media and technology present challenges to children's growth. This study uses qualitative methods with data collection technique to process it as research material. This data is sourced from several relevant journals, then selected, processed, presented, discussed, and finally complied into a single conclusion. There are various negative impacts that can affect children's health, development, safety, behavior, concentration, and brain function. Early childhood education aims to stimulate all aspects of a child's development by providing enjoyable play activities that support the integration of their abilities optimally. Language development in early childhood plays a central role in their lives. However, the use of Gawais can influence children's language skills, sosial interaction, health, information acquisition, and knowledge. These skills typically develop through a series of stages including habituation, listening, speaking, reading, and writing. Parents play a crucial role in monitoring, controlling, and observing children's activities to ensure their optimal growth.